Novel types of supra soft operators via supra soft sd-sets and applications - Alaa M. Abd El-latif (AIMS Mathematics, 2024)
Our purpose in this work is to present a new generalized soft open set in supra soft topological spaces, named supra soft sd-sets. With deep discussion, we found out that they contain almost all kinds of weaker supra soft open sets which have been discussed in earlier studies, as shown in the following figure.